Nontyphoidal Salmonella purulent pericarditis presenting with pericardial tamponade in a patient on infliximab therapy. (2019) - Saddler, Kimberly; Castro-Lainez, Miriams T; Deliz-Aguirre, Rafael; Muñoz, Julieta; Aguilar Espinal, Jorge Augusto; Sierra-Hoffman, Miguel; Chandna, Harish; Howel, Alan; Midturi, John; Winn, Richard
Abstract: Infection with nontyphoidal Salmonella is traditionally characterized by intestinal manifestations. However, extra-intestinal infections are known to occur, with purulent pericarditis associated with cardiac tamponade being rare. This case report is of a 57-year-old male with Crohn's disease initiated on infliximab therapy two months prior to presentation. He presented with recurrent chest pain and a single occurrence of fever. A Computed Tomography (CT) scan of the chest revealed a pericardial effusion. An echocardiogram confirmed the presence of the fluid with tamponade physiology, requiring immediate surgical decompression. The pericardial fluid culture grew Salmonella enterica, despite the patient having only a single episode of fever, disproportionate to the severity of the infection. Conceivably, the lack of systemic symptoms may be attributed to recent infliximab therapy. Upon conducting a literature review, immunosuppressive factors seem to play a significant role in nontyphoid Salmonella enterica pericardial effusion presenting with cardiac tamponade.